CHATBOT SEBAGAI INOVASI PEMBELAJARAN DIGITAL: SLR TREN GLOBAL DAN NASIONAL 2020–2025 - Imanuel Felix Yafianto; Raditya Taufiqul Anugrah Pradana; Rafi Satrio Winahyu (CV. Denasya Smart Publisher, 2025)
This study analyzes the development of chatbot research in digital education during the 2020–2025 period using a Systematic Literature Review (SLR) approach on 100 publications, consisting of 40 national papers and 60 international papers. The results indicate a significant increase in the number of studies in 2023–2024, coinciding with the widespread adoption of Generative AI technologies such as ChatGPT, Gemini, and Bard. National studies predominantly focus on the development of AI chatbots and tutor chatbots for interactive learning, whereas international studies demonstrate greater diversity by exploring administrative chatbots, gamified chatbots, and Large Language Model based chatbots. Overall, chatbots have been shown to enhance learning motivation, the effectiveness of online learning, academic administrative efficiency, and the development of 21st-century skills. However, challenges remain, including ethical issues, response accuracy, academic integrity, and educators’ readiness to adopt these technologies. The synthesis of findings across studies further reveals that the successful implementation of chatbots is influenced by technological, pedagogical, interaction design, and social dynamics factors. Therefore, this study recommends the development of chatbots based on human-centered AI, the enhancement of digital literacy, and the expansion of research into underexplored domains to support the effective, ethical, and sustainable implementation of chatbots within the digital education ecosystem.